EKSPLORASI PEMAHAMAN DAN KEAKTIFAN SISWA MELALUI LKPD POP UP MENURUT ISLAM PADA MATERI PKN KELAS 6 DI SDI MIFTAHUL FALAH - Nur Ilma; Mia Audina Musyadad; Agus Jaenal (Prodi PGMI STAI Sabili Bandung, 2026)
The background of this research is based on the low student engagement and shallow conceptual understanding due to the dominance of conventional teacher-centered learning methods, so that more interactive and meaningful learning innovations are needed. This study aims to explore student conceptual understanding and learning activity through the use of Islamic value-based Pop-Up Student Worksheets (LKPD) on the material of rights and obligations in Civics learning for grade VI at SDI Miftahul Falah Karawang Timur. This research uses a qualitative approach with a case study design. The research subjects consisted of teachers and grade VI students who were selected purposely. Data collection techniques included observation, semi-structured interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, with validity testing through triangulation of sources and techniques. The results showed that the use of Islamic value-based Pop-Up Student Worksheets was able to significantly improve student conceptual understanding and learning activity. This is evident from the increase in students' average scores from 60% to 90%. Students were able to understand the concept of rights and obligations, explain their relationship, and relate them to Islamic values ​​such as honesty, responsibility, and justice. In conclusion, Islamic value-based Pop-Up LKPD is effective in increasing understanding and learning activity and creating interactive, contextual, and meaningful learning.